Formal [4+2]-annulation of vinyl azides with N-unsaturated aldimines - Zhu, Xu (2014)
Highly functionalized quinolines and pyridines could be synthesized by BF3⋅OEt2-mediated reactions of vinyl azides with N-aryl and N-alkenyl aldimines, respectively. The reaction mechanism could be characterized as formal [4+2]-annulation, including unprecedented enamine-type nucleophilic attack of vinyl azides to aldimines and subsequent nucleophilic cyclization onto the resulting iminodiazonium ion moieties.